Functional Phosphoproteomics in Cancer Chemoresistance Using CRISPR‐Mediated Base Editors. Issue 30 (31st August 2022) - Li, Jianan; Lin, Jianxiang; Huang, Shisheng; Li, Min; Yu, Wenxia; Zhao, Yuting; Guo, Junfan; Zhang, Pumin; Huang, Xingxu; Qiao, Yunbo
Abstract: Selective inhibition of targeted protein kinases is an effective therapeutic approach for treatment of human malignancies, which interferes phosphorylation of cellular substrates. However, a drug‐imposed selection creates pressures for tumor cells to acquire chemoresistance‐conferring mutations or activating alternative pathways, which can bypass the inhibitory effects of kinase inhibitors. Thus, identifying downstream phospho‐substrates conferring drug resistance is of great importance for developing poly‐pharmacological and targeted therapies. To identify functional phosphorylation sites involved in 5‐fluorouracil (5‐FU) resistance during its treatment of colorectal cancer cells, CRISPR‐mediated cytosine base editor (CBE) and adenine base editor (ABE) are utilized for functional screens by mutating phosphorylated amino acids with two libraries specifically targeting 7779 and 10 149 phosphorylation sites. Among the top enriched gRNAs‐induced gain‐of‐function mutants, the target genes are involved in cell cycle and post‐translational covalent modifications. Moreover, several substrates of RSK2 and PAK4 kinases are discovered as main effectors in responding to 5‐FU chemotherapy, and combinational treatment of colorectal cancer cells with 5‐FU and RSK2 inhibitor or PAK4 inhibitor can largely inhibit cell growth and enhance cell apoptosis through a RSK2/TP53BP1/ γ ‐H2AX phosphorylation signaling axis. It is proposed that this screen approach can be used for functional phosphoproteomics in chemotherapy of various human diseases. Abstract : A high‐throughput strategy for identifying functional phosphorylation sites involved in 5‐fluorouracil (5‐FU) resistance is introduced using clustered regularly interspaced short palindromic repeats (CRISPR)‐mediated cytosine base editor (CBE) and adenine base editor (ABE), by mutating phosphorylated amino acids with guide RNA libraries, and RSK2 and PAK4 kinases are identified as main effectors in responding to 5‐FU chemotherapy for colorectal cancer.